Comparison of Growth Traits and Yields Components of five Chickpeas Genotypes (Cicer arietinum L.) at Bakrajo/ Sulaymaniyah Conditions - Ahmed, Jalal Omer; Yara Mohammad, Dara; Rashid Abdulla, Anwar; Hama Noori Meerza, Chnar (Kurdistan Journal of Applied Research, 2018)
This study was carried out in Bakrajo Technical Institute, affiliates to the Sulaimania Polytechnic University. The investigation was done to find the relationships between genotypes and sowing times of five chickpeas (Cicer arietinum L.) during 2017-2018 seasons. Genotypes and sowing time are two significant variables which have impact on crop performance. However, heat stress throughout reproductive growth it is possible to cause Significant productivity loss. According to the environment conditions in winter season in the northern Iraq; crop meets slight heat and the acceptable moisture during reproductive growth and maturity. This leads to resulting in maximum and consistent yields, as well as there is a positive correlation between Maturity and Seed Yield (kg/h) as resulted from the experiment. Experimentation was laid out in a randomized complete blocks design (RCBD) with three replications applied. Results of analysis of variance outlined that there was significant difference between chickpeas varieties in the most of traits such as no. of branches per plant, 50 % flowering, no. of pods per plant ,leaf area , seeds weight per plant and the 100 seeds weight plus harvest index, which in turn give a share in to raise yields and yield components. Sowing time and varieties had significant effects on all measured trait, Ghab 1; Filip 2 and Filip 3 winters sowing genotypes gave higher seed yield, 1582.66, 1554.66 and 1533.33 Kg/h respectively. Minimum yield 662, 480 Kg/h was recorded in the Local and Swrka spring sowing genotype.